PENERAPAN METODOLOGI PENALARAN BERBASIS KASUS DALAM MENDIAGNOSA KERUSAKAN KOMPUTER - Sandy Kosasi (Teknik Informatika Universitas Malikussaleh, 2015)
Case-based reasoning methodology has validity of offering several solutions by searching prior knowledge and make migration of new knowledge to solve the problems. The methodology is also applied, especially to repair computer damage. The limitation of users’ knowledge on damage of computer components is a basic problem in handling the damage. This research aims to produce software diagnosing computer damage. This software also educates the public to use computers based on the standards; therefore, more severe computer damage requiring special handling is avoidable. The research result shows that the software diagnosing computer damage can work well and have guarantees of informing mistakes messages when users wrongly input the data. This software still needs further development in terms of characteristics, indications, and solutions of computer damage.